Efektifitas Penerapan Lingkungan Persalinan Dengan Terapi Komplementer (Aromaterapy, Terapi Musik Dan Terapi Relaksasi) Terhadap Penurunan Intensitas Nyeri Persalinan Kala I Fase Aktif - Emy Suryani; Siti Yulaikah (Jurnal Kebidanan dan Kesehatan Tradisional, 2016)
Abstract: Complementary Therapies, Pain Delivery. Childbirth is a process of spending the products of conception. Labor begins his existence, mucus blood and cervical dilation. There are two phases which Latin (opening 1-3 cm) and the active phase (4-10 cm opening). These phases will usually be accompanied by pain. Labor pain will be more severe if accompanied by fear, anxiety, tension and lack confidence, it is this which can aggravate the pain of labor. The application of the therapy delivery environment is expected to help mothers to penurunkan first stage of labor pain intensity active phase. The purpose of this study to determine the effectiveness of the application delivery environment with komplemeter therapy to decrease pain intensity first stage of labor active phase. The study design was a pre-experimental design with a comparison group static approach. The study population was all pregnant women who gave birth in BPM Yessi Aprilia and Mandy Widowati Kleten district in 2015, while the sample is multigravida mothers who gave birth in January 1 to June 6 2015 some 40 maternal. Sampling technique used was purposive sampling. Data collection techniques using the Verbal Descriptor Scale. Data analysis using the Wilcoxon test. Research, the first stage of labor pain intensity in the active phase of the experimental group mostly feel the pain of labor at the level of moderate pain, by 85% in the control group while the majority (55%) of respondents feel the pain of labor at the level of severe pain. Comparison of the rate of labor pain between the experimental and control group, there were 3 women giving birth in the group of experimental declared labor pain at the level of severe pain than birth mothers in the control group, there were 7 people maternal feeling labor pains the same, either in a group experiment and the control group and there were 10 maternal in the experimental group feel the labor pain in the category of moderate pain than birth mothers in the control group. No difference in pain intensity between maternal childbirth given application delivery environment with complementary therapies to mothers who were not given the application delivery environment with complementary therapies, P = 0.052 (p> 0.05).